The Effect of The Application of Suggestopedia Teaching Method Toward Students’ Speaking Ability of Grade Eleven at SMA Adiguna Bandarlampung 2014 - Meidian Putri Zusana (International Conference on Education and Language (ICEL), 2014)
The objective of the research is to find out whether there is any effect of the application of Suggestopedia teaching method toward students’ speaking ability of grade eleven at SMA ADIGUNA Bandar Lampung in 2014. Suggestopedia is a teaching system which makes use of all the possibilities tender suggestion can offer. Of course, the systematic academic participation is not neglected but is always in accord with the suggestive. The unique one of this method is using music as a background in the class. The types of music are baroque and classical. In this quantitative research, the researcher uses purposive sampling to get the data and takes interview test to students’ speaking ability. In doing scope of the research, the researcher takes the subject of the research of grade eleven at SMA ADIGUNA Bandar Lampung in 2014. And the context of the research would be conducted at SMA ADIGUNA Bandar Lampung. It is located on JalanKhairil Anwar No. 79 Durian PayungTanjungkarangPusat, Bandar Lampung.